#FeesMustFall and the decolonised university in South Africa: Tensions and opportunities in a globalising world. (2019) - Griffiths, Dominic
Highlights: From 2015–2017 South African universities were gripped by student protests. The movement, known as #FeesMustFall, protested the ongoing increase of university tuition. #FeesMustFall was motivated by the twin demand of free and decolonised education. In December 2017 a policy for implementing free education was introduced. However, decolonised education in a globalised world is a more challenging, elusive goal. Abstract: Colonialism's legacy in South Africa includes persistent economic inequality which, since the country's universities charge fees, bars many from higher education, perpetuating the marginalisation of those previously disadvantaged by the apartheid regime. In 2015–6, country-wide unrest raged across university campuses, as students protested the yearly cycle of tuition increases under the slogan #FeesMustFall, demanding " free, decolonised education ". Protests ended in December 2017 when the government announced a sliding-scale payment policy alleviating the economic burden for poorer students. This paper sets the #FMF movement and its twin demands within the context of decoloniality, and argues that while free education has been achieved, imagining and implementing decolonised education for South Africa in an increasingly globalised world is a more challenging, elusive goal.